Practical Discrete Mathematics : Discover math principles that fuel algorithms for computer science and machine learning with Python /: Discover math principles that fuel algorithms for computer science and machine learning with Python. (2021) - White, Ryan T; Ray, Archana Tikayat
No abstract available